The Politics of Marriage Law in Al Jazair (Between Modernizing Family Law and Maintaining Conservative Values) - Dianati, Yusrina Nur; Tika Ifrida Takayasa (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
Algeria is one of the Muslim countries in Africa. Algeria has undergone a series of legal reforms, including in the area of family law. These reforms may include efforts to modernize the law, improve the protection of women's rights, and adapt regulations to social and cultural developments. Social and cultural values also play a role in family law in Algeria. The fundamental problem in this paper is how the political process in realizing the standardized marriage law. This article uses a political law approach with a qualitative method by describing political phenomena that occur in the State of Algeria. The conclusion in this article is that family law in Algeria is a reflection of efforts to achieve a balance between tradition and modernity, as well as between Islamic values and colonial influences. This search for harmony reflects the changing dynamics of Algerian society, where family law has become a vehicle to reflect and adapt to the changes taking place in an increasingly complex society. Although challenges remain, efforts to achieve justice, equality and resilience in family law continue to be an integral part of Algeria's journey towards a more inclusive and age-appropriate future.